Can we increase our confidence about the locations of biodiversity 'hotspots' by using multiple diversity indices?. Issue 12 (21st December 2015) - Tolimieri, N.; Shelton, A. O.; Feist, B. E.; Simon, V.
Abstract : Some have suggested that targeting conservation efforts on biodiversity hotspots—areas of exceptionally high diversity—is the most efficient way to use limited resources to protect the most or rarest species. Moreover, the preservation of biodiversity is a focus for resource management and conservation because of the links between biodiversity and ecosystem function. However, there are many ways to define biodiversity and a plethora of diversity indices. Do these indices agree on where biodiversity hotspots are, and by extension, where conservation should take place? Here we use a habitat modeling approach to map spatial and temporal patterns in five community metrics of the demersal fish community in the California Current Large Marine Ecosystem: species density, species evenness, taxonomic distinctness, functional divergence and total biomass. Depth, bottom temperature, sediment grain size, and distance to hard substratum were included as covariates in the model. All indices showed strong spatial patterns and relationships with depth. Spatial patterns for functional divergence and total biomass varied among years, but other indices did not show temporal variation. We identified hotspots as cells where at least one index was in the top 5% or 10% of its range. There was minimal spatial overlap among 10% hotspots for the five indices. Over 40% of the study area was classified as a biodiversity hotspot by at least one metric. However, no area was identified as a hotspot by all five metrics, and only slightly more than one percent of the coast was identified as within a hotspot for three or more metrics. Since different indices represent various aspects of diversity, our results caution against the uninformed use of these indices in the identification of biodiversity hotspots. Instead, we must define our objectives and then choose the relevant metrics for the problem.